RANCANG BANGUN AUTOMATIC RAIN RECORDING (ARR ) BERBASIS DEVELOPMENT BOARD MIKROAVR128 - Kurniawan Nugroho, Andi; Susilo, Edy; Setyati Budiningrum, Diah (Universitas Semarang, 2017)
The right use of rain can provide many benefits. For this reason, mapping of rainfall areas is needed. This is intended to determine the level of disaster preparedness for each region. In mapping, a tool is needed to calculate the rainfall that falls. In the market there are only manual measuring devices, while rainfall gauges are not available which can measure automatically and directly but additional equipment is needed separately. In addition, the measurement results cannot be seen by the public. Therefore we need a tool that works automatically that can display measurement results directly and can be seen directly by the public. Thus the community can see and measure rainfall that falls. In this plan Automatic Rain Recording is used by using a proximity sensor placed on top of a measuring cup and the sensor is connected to the AVR128 Development Board as the control center to convert sensor data into ADC (Analog to Digital Converter) data. This tool is connected with a microSD with a capacity of 8Gbyte to store rainfall level data. AVR128 will store every 2 minutes with a total of 275,368 data and 382 days of storage capability.Keywords : rainfall, ARR, ADC, AVR128, mikroSD